2022
DOI: 10.1093/eurheartj/ehac544.1157
|View full text |Cite
|
Sign up to set email alerts
|

Association between high sensitivity C-reactive protein and coronary atherosclerosis in a general middle-aged population

Abstract: Background Despite abundant knowledge about the relationship between inflammation and coronary artery disease (CAD), it is still unknown whether high sensitivity C-reactive protein (hsCRP) is associated with coronary atherosclerosis in the general population. Objectives The project aimed to study the association between systemic inflammation, measured as hsCRP, and coronary artery atherosclerosis in a large population based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Similar results were also found in 28 263 women using various inflammatory markers including CRP, serum amyloid A, soluble intercellular adhesion molecule type 1, and IL-6 in the Women's Health Study [41]. More recently, observational studies have confirmed that low-grade inflammation is associated with higher risk of ASCVD in different settings [42,43 ▪ ,44 ▪ ,45,46]. In the ARIC study, a community-based primary prevention study, the hazard ratio for ASCVD was 1.5 (95% CI: 1.4–1.7) in individuals within the highest tertile of IL-6 compared to the lowest tertile [43 ▪ ].…”
Section: Recent Evidencesupporting
confidence: 65%
See 1 more Smart Citation
“…Similar results were also found in 28 263 women using various inflammatory markers including CRP, serum amyloid A, soluble intercellular adhesion molecule type 1, and IL-6 in the Women's Health Study [41]. More recently, observational studies have confirmed that low-grade inflammation is associated with higher risk of ASCVD in different settings [42,43 ▪ ,44 ▪ ,45,46]. In the ARIC study, a community-based primary prevention study, the hazard ratio for ASCVD was 1.5 (95% CI: 1.4–1.7) in individuals within the highest tertile of IL-6 compared to the lowest tertile [43 ▪ ].…”
Section: Recent Evidencesupporting
confidence: 65%
“…Overall, the results of recently published observational and genetic Mendelian randomization studies support a causal association between low-grade inflammation and ASCVD (Table 1) [42,43 ▪ ,44 ▪ ,45,46,49 ▪▪ ,50 ▪▪ ,51,52 ▪▪ ,53 ▪ ,54].…”
Section: Recent Evidencementioning
confidence: 75%